2015
DOI: 10.1136/gutjnl-2014-308435
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir monotherapy versus tenofovir and entecavir combination therapy in adefovir-resistant chronic hepatitis B patients with multiple drug failure: results of a randomised trial

Abstract: NCT01639066.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 47 publications
6
81
1
7
Order By: Relevance
“…Thus, entecavir and tenofovir are equally effective. Combination of entecavir and tenofovir showed no additional benefit in a randomized study in patients with multiple drug failure, although only 18% of patients were cirrhotic [43]. …”
Section: Treatment Of Chronic Hepatitis B and Decompensated Cirrhosismentioning
confidence: 99%
“…Thus, entecavir and tenofovir are equally effective. Combination of entecavir and tenofovir showed no additional benefit in a randomized study in patients with multiple drug failure, although only 18% of patients were cirrhotic [43]. …”
Section: Treatment Of Chronic Hepatitis B and Decompensated Cirrhosismentioning
confidence: 99%
“…Therefore, rtV191I mutation may be the new resistance site to LAM. Since rt224I/V has never been reported before [13,[22][23][24][25][26], further observation of these patients might address the question whether these mutations are associated with other nucleoside analogue resistance or affect the outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study on long-term TDF treatment found no resistance detectable throughout a 7-year period [16] . Real-life studies have proven TDF retains significant activity against HBV virus in pretreated subjects with resistance to LAM, adefovir, or entecavir [17,18] . Our findings demonstrate that TDF provides a reasonable treatment modality not only for treatment-naïve HBV patients, but also for rescuing treatment-experienced cases with a high rate of genotypic resistance.…”
Section: Discussionmentioning
confidence: 99%